중국의 중단립종 쌀 생산·수출 잠재력 - 정정길 (한국농촌경제연구원, 2004)
The purpose of this study is to find out the state of rice production and exports in China, especially Japonica type rice, which is expected to make a huge impact on the rice industry in Korea, if it is imported. The study is also aimed at providing fundamental materials and informative data in setting up the rice policies in preparation for future opening of the domestic rice market. As a main grain production area, the northeast region of China has proper conditions to produce Japonica type rice. Japonica rice produced in that area is regarded as the most competitive in the international market in terms of price and quality. It has a stronger price competitiveness than the rice of the US and Australia, which are the main rice exporters. Furthermore, recently-introduced policies by the Chinese government, such as agricultural tax cut and further mechanization, have reduced production costs further. Besides, the Japonica type rice produced in the China's northeast, has strong competitiveness in quality through the application of enhanced production and processing technology. Recently, the Chinese government has made efforts to strengthen the domestic rice supply by supporting grain transportation from the northeast to main cities in the central and southern area. Even though the northeast area has the great production potential of Japonica type rice, currently it is unable to satisfy the increasing domestic demands. In this regard, there is a little possibility that China will export the rice in the near future. Researchers: Chung Chung-Gil and Li Chenggui E-mail: cgchung@krei.re.kr